The Kajian Sosiopragmatik Strategi Tindak Tutur Kritik Karakter Antagonis Ibu Jawa; Bu Tejo dalam Film Tilik - Ridho'i, Nora Dita Zakiah (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
Abstract The sociopragmatic study is one that can explore the reflection of local wisdom that can be learned by the Javanese and even nationally. This research data is working from the Short Film - Tilik (2018) by focusing on the main character who is also the antagonist, Bu Tejo. Performed with an image of cynical Javanese mothers, it is good to see how the strategy is used and what are the motivations rely upon behind the utterances. Analysis of the study of speech act of criticism strategies can be used to hone of forms this characters often use. To conduct this research, the method used is transcribing all dialogues that are focused on only Bu Tejo's dialogue. There were 81 strategies of critical speech acts classified based on the form of direct criticism speech acts and indirect criticism speech acts. Direct speech acts criticism includes negative evaluation strategies, disapproval, expressions of disagreement, identify of problems, statements of difficulty and consequences. Meanwhile, the strategy of indirect speech acts criticism are corrections, identifying standards, demanding for change, request for change, suggestions of change, expressions of certainty and asking/presupposing. In examining the narrative using these strategies, it is also discovered the social motive implied by the main character of this antagonist through his critical utterances. Keywords: Speech act of criticism, sociopragmatics, film